Ethics of development, deliberative democracy and biological citizenship - Villarroel, Raúl (Revista de Filosofía, 2013)
This article will seek to inquire into the theoretical scope and consequences and impact that the conceptions of development have had. This will be, firstly, according to a certain kind of reflection about the purposes and the means of development so called "Development Ethics". This approach must be established in order to "Deliberative Democracy". Theoretical work that has been done, also during the last decades, to improve and expand the traditional and restricted notion of "political citizenship" -in the sense of a "Biological Citizenship", according to an affirmative biopolitical concept-, gives a relevant element of judgement that makes it possible to understand in a better way how it could be conceived the confluence of Development and Deliberative Democracy.